Analysis of the As-Salam Contract in Zalora Ecommerce - Annisa Paramitha Rachman Putri*; Jumiatun Khasanah; Kartika Nur Alfiyyah; Dian Hakip Nurdiansyah (Universitas Syiah Kuala, 2023)
The times have brought the economy especially sharia, to adapt technological advances. One of these advances is the online buying and selling sector. Especially since the Covid-19 pandemic the use of e-commerce has increased. Ordering goods in online buying and selling has similarities with the as-salam contract, so it is very important to know whether the online buying and selling system is in accordance with the pillars and terms of the as-salam contract which has been determined by law. This study uses qualitative research methods with descriptive analysis based on literature studies. The researcher also uses a normative (juridical) approach and the analysis used is by using a deductive method. The results of this study are the online as-salam system on Zalora.co.id is allowed because it meets the established pillars and requirements of as-salam, it's just that it can be imperfect because sometimes there are discrepancies in the specifications, accordance with the offer or delivery of goods outside the expected agreement. After knowing the permitted as-salam system, it is better to improve the e-commerce sales mechanism, in order to minimize doubts and imperfections in the as-salam contract in online buying and selling.